2018
DOI: 10.21834/e-bpj.v3i7.1291
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Parental Feeding Attitude, Style and Environmental Factors on BMI among School Children

Abstract: Obesity prevalence has drastically increased among Malaysian population of 31 million from 15.1% in 2011 to 17.7% in 2015. Many factors can leads to overweight and obesity among school children. The objective of this study is to examine the parental feeding attitude, style and environment factor influence on body mass index among overweight and obese school children. A cross-sectional study design was conducted. The result proved that majority of the overweight and obese children because of the negative attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…SHN can assess the socioeconomic status such as education status, housing, and career to the child and family, and then make recommendations to the families on how they can change their current lifestyle habits. Similarly, the report by CDC (Centers For Disease Control And Prevention, 2014) and the World Health Organization (2014) informed that children from low socioeconomic status, negative attitude, and poor practice by parents followed by an unhealthy environment are the contributing factors to the prevalence of obesity among school children (Nordin, Said, Nordin, & Adnan, 2018). Nurses can play a significant role in educating school children about general health, healthy eating, and physical activity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SHN can assess the socioeconomic status such as education status, housing, and career to the child and family, and then make recommendations to the families on how they can change their current lifestyle habits. Similarly, the report by CDC (Centers For Disease Control And Prevention, 2014) and the World Health Organization (2014) informed that children from low socioeconomic status, negative attitude, and poor practice by parents followed by an unhealthy environment are the contributing factors to the prevalence of obesity among school children (Nordin, Said, Nordin, & Adnan, 2018). Nurses can play a significant role in educating school children about general health, healthy eating, and physical activity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the importance of understanding parental feeding practices, study in Malaysia is at an infant stage. A recent study done in 2018 by Nordin et al (2018) showed that negative parental feeding practices influenced overweight and obese children in Kuala Lumpur, Malaysia. On the other hand, improper feeding practices lead to stunting among children.…”
Section: Introductionmentioning
confidence: 99%